Peningkatan Hasil Belajar Siswa Pada Pembelajaran Ips Menggunakan Model Cooperative Tipe Student Team Achievement Divisions di Kelas V SD - gusniyeti, novi; nasrul, nasrul; mansurdin, mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to describe an increase in student learning outcomes in social studies learning using the Student Team Achievement Division (STAD) Cooperative Type model in the fifth grade of Elementary School. The approach used in this study is a qualitative and quantitative approach. This research was conducted at 34 Public Elementary Schools in Simpang Haru, Padang City with 34 students consisting of 15 women and 17 male students. The results of the study in cycle I 89.25 (B), increased in cycle II 96.4 (SB), from the aspect of the teacher and aspects of students cycle I 87.5 (B) increased in cycle II 97.5 (SB), learning outcomes students in social studies learning from aspects of attitudes, knowledge and skills in the first cycle of 77.95 were sufficient (C) to increase in cycle II 91,0 (SB)